(untitled) (Nigerian Journal of Pharmaceutical Research, 2024)
Background: Vaccines have been instrumental in thwarting the spread of infectious diseases and have been a major public health success. Community pharmacies are a critical resource for success of any immunization programme. However, pharmacists’ involvement in immunization programme in Nigeria has not been thoroughly investigated. This study assessed the involvement of pharmacists in immunization services. Methodology: A cross-sectional survey was conducted among community pharmacists, using a structured pre-tested questionnaire. The survey tool, which consisted of 72-item questions spread over five different domains, assessed vaccine availability in community pharmacies and pharmacist’s knowledge on vaccine. This (knowledge) addresses vaccine handling and administration as well as storage. The questionnaire was administered to selected community pharmacies by a combination of physical interview and electronic version through Google form link sent to pharmacist’s WhatsApp platform. Association between patients’ socio-demographics and some variables of interest was determined using Chi-square statistic. Result: One hundred and ninety-one (191) pharmacists responded to the questionnaire (99.5% response rate). About half, one hundred and three (53.93%) of the respondents were aged between 31 and 50 years. One hundred and twenty-nine (67.54%) of the pharmacists had B.Pharm degree as the highest level of education. There was a significant association between pharmacists’ age (c2 = 30.5, p<0.01), years of experience (c2 = 25.9, p<0.01), level of education (c2 = 19.6, p<0.05) and knowledge on vaccine handling and administration. Also, significant association (p<0.01) existed between pharmacists’ age (c2 = 45.1), years of experience (c2 = 45.3), level of education (c2 = 31.6) and knowledge of vaccine storage. Furthermore, there was a significant association (p<0.01) between being trained as a vaccine administrator and level of knowledge on vaccine storage (c2 = 57.8) as well as handling and administration (c2 = 45.2). Conclusion: Pharmacists’ level of education and training (as vaccine administrator) were key factors in pharmacists’ involvement in immunization care service.